An innovative strategy to create equivalent elements for modelling assembly points in joined structures. Issue 3 (28th April 2014) - Bérot, Maxime; Malrieu, Julien; Bay, François
Abstract : Purpose: – Large structures (e.g. plane, bridge, etc.) often include several hundreds of assembly points. Structural computations often use over-simplistic approximations for these points; among others, they do not take into account the thermo-mechanical history due to the assembling process. Running computations with each assembly point modelled completely would require too much time to achieve a simulation. There is thus a need to create equivalent elements for assembly points in order to: take into account the mechanical state of the assembly point in the design stage – while reducing the computational time cost at the same time. This paper aims to discuss these issues. Design/methodology/approach: – This paper introduces an innovative strategy based on a coupling procedure between a finite element tool for modelling the assembly process in order to access to the mechanical state of the assembly point and an optimisation algorithm, in order to identify the equivalent element parameters. Findings: – The strategy has proven to be successful. A connector model easier to use and much faster than the complete model, has been obtained. Results obtained with this element are in good agreement with experimental tests in the case of multipoint assemblies and with the simulation results of the complete numerical model. Finally the connector model appears to be easier to use and much faster than the complete model, more difficult to model properly. Originality/value: – The main innovative aspects of this strategy lie in the fact that the creation of this equivalent element is based on a complete numerical approach. The thermo-mechanical history due to the assembly process is considered – the element parameters are identified thanks to an evolution strategy based on the coupling between a finite element model and a zero-order minimisation algorithm.